2005
DOI: 10.1055/s-2005-861381
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Inhibition in Lactating Rats Changes Leptin Transfer through the Milk

Abstract: Malnutrition during lactation reduces milk production and changes pup's leptin serum levels. To test prolactin role in this nutritional state, we evaluated whether prolactin suppression during lactation changes serum leptin in dams, its transfer through the milk, and pup's serum leptin. Lactating rats were treated with bromocryptine (1 mg/twice a day, s.c.) or saline three days before sacrifice (days 2-4 or days 19-21). Food intake and body weight were measured until sacrifice (4th and 21st day). Serum prolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 32 publications
7
67
1
Order By: Relevance
“…Here, serum prolactin levels were positively correlated with mammary gland mass, as well as with asymptotic food intake and MEO during the 1st lactation period. Thus, serum prolactin levels are likely to be involved in the regulation of food intake during the peak lactation period and become a potential factor involved in limits to SusEI, a concept which is consistent with the prediction of the saturated neural control hypothesis (Sauve and Woodside, 2000;Bonomo et al, 2005;Speakman and Król, 2005;Zhao et al, 2010a). However, in the present study such significant correlations were not observed in the females during the 2nd, 3rd or 4th lactation periods.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Here, serum prolactin levels were positively correlated with mammary gland mass, as well as with asymptotic food intake and MEO during the 1st lactation period. Thus, serum prolactin levels are likely to be involved in the regulation of food intake during the peak lactation period and become a potential factor involved in limits to SusEI, a concept which is consistent with the prediction of the saturated neural control hypothesis (Sauve and Woodside, 2000;Bonomo et al, 2005;Speakman and Król, 2005;Zhao et al, 2010a). However, in the present study such significant correlations were not observed in the females during the 2nd, 3rd or 4th lactation periods.…”
Section: Discussioncontrasting
confidence: 48%
“…There is considerable evidence that prolactin is involved in the regulation of food intake. Thus, it may represent a potential new factor associated with neuroendocrine mechanisms underlying limits to SusEI during the lactation period (Noel and Woodside, 1993;Sauve and Woodside, 2000;Bonomo et al, 2005;Speakman and Król, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Early weaning changes serum leptin levels in weaned animals (Bonomo et al 2005, Lima et al 2011. This early change in the leptin level is critical for establishing neural circuitry in the hypothalamus (Bouret et al 2004) at a different set point of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…At weaning, dams were separated from their litters and, 2 h later, milk was collected and stored at K20 8C until assayed (Bonomo et al 2005). After that, S and C dams and pups were killed, and blood was collected.…”
Section: Detection Of Cotinine (Nicotine Metabolite)mentioning
confidence: 99%
“…For this, mothers were separated from litters for 2 h before milking (Bonomo et al 2005). After i.p.…”
Section: Milk Collectionmentioning
confidence: 99%